Method for preparing polymer film and polymer film prepared by method

Through the combination of electrospinning film and mid-infrared high-reflection functional materials, the dilemma between passive radiation heating performance and wearability of the high-reflection composite warm-keeping film is solved, and a crack-free, high-reflection, moisture-permeable composite warm-keeping is achieved. The membrane improves the local heating effect and wearable performance of the human body.

CN119265802APending Publication Date: 2025-01-07KINGS FLAIR INNOVATIVE MARKETING LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310813124.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-04
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

In the prior art, the high-reflection composite warm-insulating film has a dilemma between optimal passive radiant heating performance and good wearability, and cannot have sufficient infrared reflectivity to hinder the loss of heat energy in the human body and a comfortable wearing experience.

Method used

Using the combination of electrospinning film and mid-infrared high-reflection functional material, the film is enhanced by depositing metal carbides on the polymer film to form a crack-free high-reflection composite warm-keeping film. warmth, moisture permeability and mechanical properties.

Benefits of technology

It has achieved improvements in warming performance, moisture permeability and mechanical properties, ensuring the crack-free characteristics and good wearable performance of the membrane, significantly improving the local heating effect of the human body, and is suitable for warm, moisture permeable clothing and smart wearable fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265802A_ABST
    Figure CN119265802A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a polymer membrane. The method comprises the following steps: i) forming at least one polymer into a first membrane through an electrospinning technology; ii) dispersing at least one metal carbide in a first liquid to form a first mixture; iii) filtering the first mixture wherein the first membrane is used as a filtration membrane, whereby the at least one metal carbide is deposited on the first membrane to form a second membrane; and iv) drying the second film to form a third film; the method is characterized in that the at least one polymer can be selected from polyvinylidene fluoride and / or polyurethane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a crack-free high-reflection composite thermal insulation film (also known as a crack-free low-emission thermal insulation film) and a preparation method thereof, and in particular to a crack-free high-reflection composite thermal insulation film containing a mid-infrared high-reflection functional material and a preparation method thereof. Background Art

[0002] Indoor heating of residential and commercial buildings accounts for a large part of the total energy consumption worldwide. For example, 47% of global energy is still used for indoor heating alone, of which 42% is specifically used for heating residential buildings. To reduce indoor heating, existing technologies usually focus on improving the insulation requirements of buildings rather than focusing on people. If heating and insulation can be managed directly according to people's conditions, a large amount of energy can be saved. Energy-saving methods of managing heating and insulation directly according to people's conditions are called "personal thermal management", which mainly performs local thermal control of the direct environment around the human body to alleviate the energy demand for indoor temperature regulation. Therefore, the development of materials and systems that can heat the human body temperature in an energy-saving manner is extremely urgent to alleviate the energy crisis and global warming.

[0003] Generally speaking, the human body, with a normal skin temperature of about 34°C, mainly emits mid-infrared radiation in the wavelength range of 7-14μm (also known as the atmospheric window), and about 60% of the heat generated by the human body is dissipated through infrared radiation. Maintaining the human body temperature at a relatively constant level through heating is crucial to maintaining thermal comfort and various biological processes of the human body.

[0004] Conventional textiles only act as an insulating layer, preventing heat conduction and convection, but have no ability to dissipate heat radiatively. Conventional textiles exhibit high mid-infrared emissivity, so the heat generated by the human body can be easily transported to the cold outside space through conventional textiles.

[0005] Passive radiative heating is primarily a method of blocking the loss of heat from an object through the atmospheric window to outer space in a non-energy-intensive manner, and is a promising approach to addressing the problem of excessive energy consumption. Further energy savings are expected through the development of passive radiative heating textiles. Therefore, it is possible to significantly alter the local heating of the human body indoors by manipulating infrared radiation by adjusting the thermal radiation properties of textiles.

[0006] However, there is still a lack of an ideal passive radiation heating textile that has both optimal passive radiation heating capabilities and good wearability. This is mainly reflected in the combination of materials with thermal insulation functionality and textiles formed by wearable films, that is, for example, whether the thermal insulation functional material can be evenly present on the surface of the wearable film, whether there are cracks in the wearable film, whether it affects the moisture permeability, whether it affects its inherent mechanical properties, etc.

[0007] Although there are very few radiative heating textiles on the market, these textiles have serious defects and cannot combine warmth retention and meet the basic indicators related to wearable performance. For example, Mylar blankets, which consist of a solid plastic sheet coated with a dense metal reflective film, lack breathability, making them uncomfortable for daily wear. Omni-Heat technology prints sparse metal dots on the inside of the garment to reflect body heat, but the technology suffers from low reflectivity and poor passive radiative heating performance. Recently developed silver nanowire-coated textiles have a low infrared reflectivity of about 40%, and the temperature rise of the human body is only 0.9℃ higher than that of ordinary textiles. In addition, a nanophotonic structure textile was fabricated by depositing gold and germanium coatings on the dopamine hydrochloride (PDA) treated surface of polyethylene, which improved the local heating performance by 3.8℃, but the mechanical properties were poor (elongation strain rate was less than 40%).

[0008] In view of the wearable high-reflective composite thermal insulation film in the prior art, the thermal material obtained always faces a dilemma between the best passive radiation heating performance and good wearability. First, there is not enough infrared reflectivity to hinder the local heat loss of the human body. Second, it is required to have a comfortable wearing experience without affecting the thermal management performance.

[0009] In summary, the present invention provides a crack-free high-reflection composite thermal insulation film (hereinafter referred to as "the composite thermal insulation film of the present invention") based on an electrospinning membrane and containing a mid-infrared high-reflection functional material and a preparation method thereof. The film introduces an electrospinning membrane and a mid-infrared high-reflection functional material, which is used as a mid-infrared reflector for temperature regulation technology and has mid-infrared high-reflection characteristics, so that the film has good thermal insulation performance, tensile breaking strength, moisture permeability and wearable advantages. The composite thermal insulation film of the present invention is expected to become a promising textile material for optimizing mid-infrared emissivity, and is used in the fields of thermal insulation, moisture permeable clothing, architectural structure cloth membranes and smart wearables. Summary of the invention

[0010] A first aspect of the present invention relates to a method for preparing a polymer film, comprising the following steps:

[0011] i) forming at least one polymer into a first film by electrospinning technology;

[0012] ii) dispersing at least one mid-infrared high reflective material in a first liquid to form a first mixture;

[0013] iii) filtering the first mixture, wherein the first membrane is used as a filtering membrane, thereby depositing the at least one metal carbide on the first membrane to form a second membrane; and

[0014] iv) drying the second film to form a third film.

[0015] In one embodiment, the at least one polymer may be selected from polyvinylidene fluoride and / or polyurethane.

[0016] In one embodiment, in method step i), the at least one polymer is dissolved in a solvent at 50-80°C.

[0017] Preferably, the concentration of the at least one polymer in the solvent is 50% by weight or less.

[0018] Preferably, the concentration of the at least one polymer in the solvent is 30% by weight or less.

[0019] Preferably, the concentration of the at least one polymer in the solvent is 15-30% by weight.

[0020] Preferably, the concentration of the at least one polymer in the solvent is 5-30% by weight.

[0021] Preferably, the solvent is a dimethylformamide solution.

[0022] In one embodiment, the mid-infrared high reflective material is metal carbide.

[0023] In one embodiment, the concentration of the at least one metal carbide in the first liquid is 2% by weight or less.

[0024] Preferably, the concentration of the at least one metal carbide in the first liquid is 0.1% by weight or less.

[0025] Preferably, the concentration of the at least one metal carbide in the first liquid is 0.02% by weight or less.

[0026] Preferably, the concentration of the at least one metal carbide in the first liquid is 0.01-0.05% by weight.

[0027] Preferably, the particle size of the at least one metal carbide is 5 μm or less.

[0028] Preferably, the particle size of the at least one metal carbide is 0.2-1 μm.

[0029] Preferably, the particle size of the at least one metal carbide is 0.1-1 μm.

[0030] In one embodiment, the at least one metal carbide is titanium carbide.

[0031] Preferably, the first liquid is water; and in method step ii), titanium carbide is dispersed in water at a concentration of 10-20 mg / ml.

[0032] Preferably, the particle size of titanium carbide is 0.1-1 μm.

[0033] Preferably, the concentration of titanium carbide in the first liquid is 0.05% by weight or less.

[0034] Preferably, the concentration of titanium carbide in the first liquid is 0.01-0.02% by weight.

[0035] In one embodiment, in method step iii), the filtration is vacuum filtration.

[0036] In one embodiment, in method step i), 50% by weight or less of the at least one polymer is dissolved in 50% by weight or more of a dimethylformamide organic solvent, and in method step ii), the concentration of the at least one metal carbide in the first liquid is 0.05% by weight or less.

[0037] In one embodiment, in method step i), 50% by weight or less of the at least one polymer is dissolved in 80% by weight of dimethylformamide organic solvent, and in method step ii), the concentration of the at least one metal carbide in the first liquid is 0.05% by weight or less.

[0038] The second aspect of the present invention relates to a polymer film prepared according to the method for preparing a polymer film as described in the first aspect, characterized in that the weight ratio of the mid-infrared high reflective material in the third film is 10%.

[0039] Advantageously, the third film has at least one of the following physical properties:

[0040] –Thickness: 0.01-0.02mm;

[0041] – According to GB / T 2423.1 standard, the warm temperature is >4℃;

[0042] – Moisture permeability>10000g·m2 / 24h; and

[0043] –Breaking strength>12MPa.

[0044] Advantageously, said third film is crack-free. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] The present invention provides the following drawings, which are intended to describe various embodiments of the present invention in detail, but are not intended to limit the present invention, wherein:

[0046] Figure 1 The present invention is a process flow chart for preparing the composite thermal insulation film of the present invention.

[0047] Figure 2 Thermal imaging camera image of thermal performance. DETAILED DESCRIPTION

[0048] The present disclosure is now presented in an exemplary manner with reference to the accompanying drawings in the following paragraphs. The objects, features and aspects of the present disclosure are disclosed in or are apparent from the following description. It should be understood by those of ordinary skill in the art that the following discussion is only a description of exemplary embodiments, which is only to further illustrate the features and advantages of the present invention, rather than to limit the present invention.

[0049] Unless otherwise specified, all chemicals described herein are commercially available and used as received without special processing, which may include impurities such as residual solvents or by-products.

[0050] In an embodiment, the content of the polymer is 5-30 parts by weight, and is not equal to 0.

[0051] In an embodiment, the mid-infrared high reflection functional material is selected from titanium carbide, the size of the mid-infrared high reflection functional material is 0-5 μm, and the content of the mid-infrared high reflection functional material is 0-0.1 parts by weight.

[0052] Figure 1 The present invention relates to an overview of a method for preparing the composite warming film of the present invention, which comprises the following steps:

[0053] 1) Dissolve 5-30% by weight of a polymer in 70-95% by weight of a dimethylformamide organic solvent and stir at 60° C. to obtain an electrospinning solution;

[0054] 2) forming an electrospinning solution into a film by using an electrospinning technique to obtain an initial polymer film;

[0055] 3) dispersing 0-0.02% by weight of titanium carbide in an aqueous solution to obtain a 10 mg / ml-20 mg / ml titanium carbide solution;

[0056] 4) The initial polymer film is used as a filter membrane, and the titanium carbide solution is deposited on the electrostatically spun film by using a vacuum filtration technique, and the composite thermal insulation film of the present invention is obtained after drying.

[0057] In the above specific preparation process, the polymer is first dissolved in a solvent according to the composition ratio, and an electrospinning solution is obtained after stirring. In this process, the above raw materials are preferably placed at 60°C and stirred at high speed until the polymer is completely dissolved, thereby obtaining an electrospinning solution. In a specific embodiment, the solution is selected from a dimethylformamide solution. In this embodiment, the above solution is selected to fully dissolve the polymer, and the solution does not contain highly toxic chemicals, and the prepared product has low toxic residue and low environmental pollution.

[0058] After obtaining a fully dissolved polymer electrospinning solution, the polymer solution is formed into a film using electrospinning technology to obtain an initial film; the above electrospinning process is a technical means well known to those skilled in the art, and the present invention has no particular limitation on this. For example, the electrospinning parameters can be: the electrospinning voltage is 18KV, the syringe propulsion rate is 0.5mL / h, and the collection distance is 15cm.

[0059] A certain proportion of titanium carbide high reflective functional material powder is uniformly dispersed in 10 ml of aqueous solution to obtain a titanium carbide solution. The above dispersion process is a technical means well known to those skilled in the art, and the present invention has no particular limitation on this. For example, the dispersion process can be selected from an ultrasonic dispersion process.

[0060] Finally, the present invention uses the initial film obtained as a filter membrane, and filters the titanium carbide solution through a vacuum filtration technology, and obtains a composite thermal insulation film after drying.

[0061] After the above preparation method, the composite thermal insulation film prepared by the present invention has a thickness of 0.01-0.02 mm and a moisture permeability of >10000 g·m 2 / 24h, thermal insulation performance>4℃.

[0062] In order to further understand the present invention, the following specific examples provide a more detailed description of the crack-free high-reflective composite thermal insulation film and the preparation method thereof.

[0063] Example 1: Preparation of polyvinylidene fluoride-polymer film

[0064] First, 80% by weight of dimethylformamide solution was vigorously dispersed in a flask.

[0065] Then, 20% by weight of polyvinylidene fluoride was slowly added to 80% by weight of dimethylformamide solution at 60°C with vigorous stirring. Then, through electrospinning technology, a plastic syringe containing a uniform polymer solution (5 ml) was used, and the electrospinning parameters were adjusted, with an applied voltage of 20 kV and a syringe speed of 1 ml / h, and the distance between the rolling collector and the syringe needle was set to 15 cm. A polyvinylidene fluoride-polymer film with a thickness of 0.015 mm was prepared.

[0066] Example 2: Preparation of polyvinylidene fluoride / polyurethane-polymer film

[0067] First, 80% by weight of dimethylformamide solution was vigorously dispersed in a flask.

[0068] Then, 10% by weight of polyvinylidene fluoride and 10% by weight of polyurethane were slowly added to the dimethylformamide solution under vigorous stirring at 60°C. Then, by electrospinning technology, a plastic syringe containing a uniform polymer solution (5 ml) was used, and the electrospinning parameters were adjusted, with an applied voltage of 20 kV and a syringe speed of 1 ml / h, and the distance between the rolling collector and the syringe needle was set to 15 cm. A polyvinylidene fluoride / polyurethane-polymer film with a thickness of 0.012 mm was prepared.

[0069] Example 3: Preparation of polyurethane-polymer film

[0070] First, 80% by weight of dimethylformamide solution was vigorously dispersed in a flask.

[0071] Then, 20% of the polyurethane by weight was slowly added to the dimethylformamide solution under vigorous stirring at 60°C. Then, by electrospinning technology, a plastic syringe containing a uniform polymer solution (5 ml) was used, and the electrospinning parameters were adjusted, with an applied voltage of 20 kV and a syringe speed of 1 ml / h, and the distance between the rolling collector and the syringe needle was set to 15 cm. A polyurethane-polymer film with a thickness of 0.010 mm was prepared.

[0072] Example 4: Preparation of polyvinylidene fluoride-crack-free high-reflective composite thermal insulation film

[0073] First, 80% by weight of dimethylformamide solution was vigorously dispersed in a flask.

[0074] Then, 20% of polyvinylidene fluoride by weight was slowly added to the dimethylformamide solution under vigorous stirring at 60°C. Then, through electrospinning technology, a plastic syringe containing a uniform polymer solution (5ml) was used, and the electrospinning parameters were adjusted, with an additional voltage of 20kV and a syringe speed of 1ml / h. The distance between the rolling collector and the syringe needle was set to 15cm. Finally, an electrospun polyvinylidene fluoride film was obtained.

[0075] Then, 0.01% titanium carbide powder was added to 10ml of aqueous solution, and a uniform titanium carbide solution was obtained by ultrasonic process. Finally, a 5*5cm electrospun polyvinylidene fluoride film was used as a filter membrane, and titanium carbide molecules were deposited on the electrospun polyvinylidene fluoride film by vacuum filtration, and then dried in a vacuum oven at 30°C for 24 hours to prepare a polyvinylidene fluoride-crack-free high-reflection composite thermal insulation film with a thickness of 0.02mm.

[0076] Thermogravimetric analysis results show that the weight ratio of titanium carbide in the composite thermal insulation film of the present invention is about 10%.

[0077] Example 5: Preparation of polyvinylidene fluoride / polyurethane-crack-free high-reflection composite thermal insulation film

[0078] First, 80% by weight of dimethylformamide solution was vigorously dispersed in a flask.

[0079] Then, 10% by weight of polyvinylidene fluoride and 10% by weight of polyurethane were slowly added to the dimethylformamide solution under vigorous stirring at 60°C. Then, through electrospinning technology, a plastic syringe containing a uniform polymer solution (5ml) was used, and the electrospinning parameters were adjusted, with an additional voltage of 20kV and a syringe speed of 1ml / h. The distance between the rolling collector and the syringe needle was set to 15 cm. Finally, an electrospun polyvinylidene fluoride / polyurethane film was obtained.

[0080] Then, 0.02% titanium carbide powder was added to 10ml of aqueous solution, and a uniform titanium carbide solution was obtained by ultrasonic process. Finally, a 5*5cm electrospun polyvinylidene fluoride film was used as a filter membrane, and titanium carbide molecules were deposited on the electrospun polyvinylidene fluoride film by vacuum filtration, and then dried in a vacuum oven at 30°C for 24 hours to prepare a polyvinylidene fluoride / polyurethane-crack-free high-reflection composite thermal insulation film with a thickness of 0.018mm.

[0081] Thermogravimetric analysis results show that the weight ratio of titanium carbide in the composite thermal insulation film of the present invention is about 10%.

[0082] Example 6: Preparation of polyurethane-crack-free high-reflective composite thermal insulation film

[0083] First, 80% by weight of dimethylformamide solution was vigorously dispersed in a flask.

[0084] Then, 20% polyurethane by weight was slowly added to the dimethylformamide solution under vigorous stirring at 60°C. Then, through electrospinning technology, a plastic syringe containing a uniform polymer solution (5ml) was used, and the electrospinning parameters were adjusted, with an additional voltage of 20kV and a syringe speed of 1ml / h. The distance between the rolling collector and the syringe needle was set to 15cm. Finally, an electrospun polyurethane film was obtained.

[0085] Then, 0.01% titanium carbide powder was added to 10ml of aqueous solution, and a uniform titanium carbide solution was obtained by ultrasonic process. Finally, a 5*5cm electrospun vinyl fluoride film was used as a filter membrane, and titanium carbide molecules were deposited on the electrospun vinyl fluoride film by vacuum filtration, and then dried in a vacuum oven at 30°C for 24 hours to prepare a polyurethane-crack-free high-reflection composite thermal insulation film with a thickness of 0.015mm.

[0086] Thermogravimetric analysis results show that the weight ratio of titanium carbide in the composite thermal insulation film of the present invention is about 10%.

[0087] Performance Testing

[0088] The polymer films prepared in Examples 1-3 and the crack-free high-reflective composite thermal insulation films prepared in Examples 4-6 were tested in terms of thermal insulation performance, water vapor permeability (WVP), and breaking strength.

[0089] The thermal insulation performance test adopts GB / T 2423.1 standard and is tested by German TESTO 871 infrared thermal imager. The film prepared in Examples 1-6 is covered on a palm with a relatively constant temperature. The infrared thermal imager can automatically collect the surface temperature of the object being tested and image the measured temperature, and then process, analyze, store and output the image. Figure 2 Thermal imaging camera image of thermal insulation performance.

[0090] The water vapor permeability test was conducted using the ASTM E96 BW standard in a Haida HD-100T constant temperature and humidity chamber (the constant temperature and humidity chamber conditions were set at: temperature 23° C., relative humidity 50%).

[0091] The tensile strength at break test was conducted using an Instron 5566 tensile testing machine (the conditions of the tensile testing machine were set at: temperature 23° C., relative humidity 50%) using the ASTM D 882 standard.

[0092] The polymer films prepared in Examples 1-3 and the crack-free high-reflective composite thermal insulation films prepared in Examples 4-6 were tested for thermal insulation performance, moisture permeability, and breaking strength. The results are shown in Table 1:

[0093]

[0094] By comparing Examples 1 and 4, 2 and 5, and 3 and 6, it can be seen from the results of thermal insulation performance that with the addition of high-reflection functional materials, the thermal insulation temperature of the resulting film will be increased from about 1.4°C to 4.8°C. It can be seen that with the addition of high-reflection functional materials, the thermal insulation performance of the resulting film is significantly enhanced. Specifically, this is because the introduction of mid-infrared high-reflection functional materials changes the molecular bond vibration of the infrared wavelength in the film, with less bond vibration, low mid-infrared emissivity, and high reflectivity. Adding mid-infrared high-reflection functional materials to crack-free high-reflection composite thermal insulation films can improve heat loss within the radiation range of the human body.

[0095] In Examples 4-6, the composite thermal insulation film of the present invention comprises a highly reflective functional material such as titanium carbide. Titanium carbide is a known ceramic material and has an affinity for the polymer selected by the present invention, such as polyvinylidene fluoride / polyurethane, and can therefore form supramolecular bonds such as electrostatic and / or hydrogen bonds with the polymer. For example, when the selected polymer is or comprises polyvinylidene fluoride, the titanium carbide is attached to the polymer surface by electrostatics between the titanium carbide and the polymer. For example, when the selected polymer is or comprises polyurethane, the polyurethane contains abundant urethane groups to form supramolecular bonds with the functional material, and the regulation of the polyurethane matrix structure by the highly reflective functional material can improve the binding force with the highly reflective functional material, and can provide good mechanical properties that are conducive to the improvement of wearable performance.

[0096] Therefore, the present invention can change the structure of the polymer by adding a highly reflective functional material such as titanium carbide, thereby enhancing the mechanical properties, so that the composite thermal insulation film of the present invention does not have a crack structure, and large layers of highly reflective material will not fall off during use, thereby avoiding the problem of reduced thermal insulation performance in later use.

[0097] The polymer film was prepared by electrospinning technology, which changed the micron-level pore size of the polymer film and formed a strong bonding force between the fibers during the fiber stretching process, thereby improving and adjusting the film's thermal insulation performance, moisture permeability, breaking strength and mechanical properties, so that the film has good wearable performance. From the test results in Table 1, it can be seen that the moisture permeability is maintained at 6900g·m 2 d -1 The breaking strength is maintained above 7.5 MPa.

[0098] By comparing Example 1 with Examples 4-6, it can be seen that as the content of the high-reflection functional material increases, the thermal insulation performance of the obtained film tends to increase first.

[0099] Specifically, when the weight ratio of the high-reflective functional material to the polymer material is within the overall range of 0-0.05:0-30, when the weight ratio of the high-reflective functional material to the polymer material is 0.01-0.02:10-30 (see Examples 4-6), the thermal insulation performance of the film can be further improved, and the thermal insulation temperature can be increased from about 1.4°C to above 4.0°C. At the same time, the moisture permeability is maintained at 6900g·m 2 d -1 The breaking strength is maintained above 12.0 MPa.

[0100] Furthermore, when the weight ratio of the high reflective functional material to the polymer material is 0.01-0.02:5-30 (see Examples 5-6), the moisture permeability of the film can be further improved, and the moisture permeability can be increased to 12000 g·m 2 / 24h or more, at the same time, the breaking strength reaches more than 12.0MPa.

[0101] Furthermore, when the weight ratio of the high reflective functional material to the polymer material is 0.01-0.02:15-30 (see Example 6), the moisture permeability and breaking strength of the film can be further improved, and the moisture permeability can be increased to 16000g·m 2 / 24h or more, at the same time, the breaking strength reaches more than 15.0MPa.

[0102] The present invention can prepare a crack-free high-reflection composite thermal insulation film with different thermal insulation properties, excellent moisture permeability, stronger mechanical properties, and better wear resistance by controlling different proportions of polymers and high-reflection functional materials. In addition, the design process for preparing the crack-free high-reflection composite thermal insulation film in the present invention is streamlined, the process is simple, and it is easy to realize industrialization.

[0103] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be noted that for ordinary technicians in the technical field, without departing from the principle of the present invention, the present invention can also be improved and modified in several ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the textual expression of the claims, or if they include equivalent structural elements that are not substantially different from the textual expression of the claims, then these other embodiments should also be included in the scope of the claims. It should be understood that each specific numerical point of the parameter described in the embodiments in the context (for example: weight ratio, particle size, temperature, etc.) can be used as the end value of the numerical range of the parameter described in the embodiments of the present invention. In other words, the end value is also included in the numerical range. It should also be understood that in the embodiments according to the present invention, each numerical value in the numerical range can also be the end value of another numerical range of the parameter.

Claims

1. A method for preparing a polymer film, comprising the following steps: i) forming at least one polymer into a first film by electrospinning technology; ii) dispersing at least one mid-infrared reflective material in a first liquid to form a first mixture; iii) filtering the first mixture, wherein the first membrane is used as a filter membrane, thereby depositing the at least one mid-infrared reflective material on the first membrane to form a second membrane; and iv) drying the second film to form a third film; It is characterized in that The at least one polymer may be selected from polyvinylidene fluoride and / or polyurethane.

2. The method for preparing a polymer film according to claim 1, characterized in that: In step i), the at least one polymer is dissolved in a solvent at 50-80°C.

3. The method for preparing a polymer film according to claim 2, characterized in that: The concentration of the at least one polymer in the solvent is 50% by weight or less.

4. The method for preparing a polymer film according to claim 2, characterized in that: The concentration of the at least one polymer in the solvent is 15-30% by weight.

5. The method for preparing a polymer film according to claim 2, characterized in that: The concentration of the at least one polymer in the solvent is 5-30% by weight.

6. The method for preparing a polymer film according to claim 2, characterized in that: The solvent is dimethylformamide solution.

7. A method for preparing a polymer film according to any one of claims 1 to 6, characterized in that The at least one mid-infrared reflecting material is a metal carbide.

8. The method for producing a polymer film according to claim 7, characterized in that The concentration of the metal carbide in the first liquid is 2% by weight or less.

9. The method for producing a polymer film according to claim 7, characterized in that The concentration of the metal carbide in the first liquid is 0.1% by weight or less.

10. The method for producing a polymer film according to claim 7, characterized in that The concentration of the metal carbide in the first liquid is 0.01-0.05% by weight.

11. The method for producing a polymer film according to claim 7, characterized in that The particle size of the metal carbide is 5 μm or less.

12. The method for producing a polymer film according to claim 7, characterized in that The particle size of the metal carbide is 0.1-1 μm.

13. A method for producing a polymer film according to any one of claims 8 to 12, characterized in that The metal carbide is titanium carbide.

14. The method for preparing a polymer film according to claim 13, characterized in that: The first liquid is water; and in step ii), titanium carbide is dispersed in the water.

15. The method for preparing a polymer film according to claim 14, characterized in that: The particle size of titanium carbide is 0.1-1 μm.

16. The method for preparing a polymer film according to claim 14 or 15, characterized in that: The concentration of titanium carbide in the first liquid is 0.05% by weight or less.

17. The method for preparing a polymer film according to claim 14 or 15, characterized in that: The concentration of titanium carbide in the first liquid is 0.01-0.02% by weight.

18. The method for preparing a polymer film according to claim 1, characterized in that: In step iii), the filtration is vacuum filtration.

19. A polymer film prepared by the method for preparing a polymer film according to any one of claims 1 to 18, characterized in that: The weight ratio of the at least one mid-infrared reflective material in the third film is 10%.

20. A polymer film according to claim 19, characterized in that The third film has at least one of the following physical properties: –Thickness: 0.01-0.02mm; – According to GB / T 2423.1 standard, the warm temperature is >4℃; – Moisture vapor transmission rate>10000g·m 2 / 24h; and –Breaking strength>12MPa.

21. A polymer film according to claim 19, characterized in that The third film is crack-free.

Citation Information

Patent Citations

  • Preparation method of thermoplastic polyurethane nanofiber membrane

    CN108049026A

  • Multifunctional flexible sensing fiber membrane and preparation method and application thereof

    CN111118889A

  • Preparation method of fiber-based anisotropic stretchable conductor

    CN113782278A

  • Collagen-based waterproof moisture-permeable film as well as preparation method and application thereof

    CN115897064A

  • Laminated body including chitin-chitosan based material

    JP2008162098A